Mengembangkan Jiwa Kewirausahaan dan Kemandirian Siswa melalui Project Based Learning Home Industry dalam Era Milenial - Fathonah (Jurnal Ilmiah Profesi Guru (JIPG), 2020)
The future generation will face increasingly fierce competition in the millennial era. Students are expected to have some competence and sensitivity to the development of science and technology to become a problem solver and be ready to face millennial challenges. This research method is descriptive qualitative analysis in the form of the results of a literature review related to Project Based Learning, home industry, entrepreneurship and independence. Data collection techniques using observation, and literature review techniques. The implementation of educational center needs to be optimized in order to give birth to a generation that has a spirit of entrepreneurship and independence in this era. Teachers can become student center-based learning facilitators through project based learning home industries. In addition, it can also connect students with the family education environment, namely parents, so that they can help students develop an entrepreneurial spirit and independence